EMPOWERING FUTURE ENGINEERS WITH CROSSCULTURAL COMMUNICATION: ERASMUS+, FULBRIGHT, AND ENGLISH LANGUAGE CLASSROOM ACTIVITIES - Nykyporets , Svitlana; Kriutchenko , Olena (Collection of scientific papers «ΛΌГOΣ», 2025)
This article explores the critical role of cross-cultural communication and specialized language instruction in modern engineering education. As technical expertise alone is no longer sufficient, the integration of intercultural competence is essential for effective global collaboration. Programs like Erasmus+ and Fulbright enhance international engagement, yet their success depends on targeted preparation by foreign language educators. Drawing on case studies from Ukraine, Germany, and Canada, the article presents evidence-based strategies for embedding linguistic and cultural training into engineering curricula. These approaches improve student readiness for international projects and foster globally competent graduates.